(untitled) (Journal of Educational Sciences, 2023)
This article examines the readiness of future special teachers for professional activity by means of coaching technology. Special attention is paid to innovative processes in the field of education and the peculiarities of the innovation being introduced, as well as to the innovative development in potential environment of the teaching staff at university. The innovation in this article is “coaching”, which creates conditions for the formation of an activity subject capable of realizing his professional potential. Coaching technology is a method of counseling and training during which helps a student to achieve a clearly defined professional and life goal. In other words, coaching in the learning process helps the student to achieve the desired result. Therefore, the use of coaching technology at the present stage is relevant in the training of special teachers. In scientific work, coaching is a unique technique created at the intersection of philosophy, psychology, management and logic, used to increase the effectiveness and disclosure of a person’s potential, to solve his business and personal problems. The elements of the content of innovative methods and forms of teaching are analyzed, the use of which will make the process of forming the readiness of future special teachers purposeful and more effective. One of the stages of the study was the primary psychological and pedagogical diagnostics with the use of coaching technology. 72 students of Auezov South Kazakhstan University were surveyed. The elements of the content of innovative methods and forms of education are analyzed, the use of which will make the process of forming the readiness of future special teachers purposeful and more effective. Key words: coaching, coaching technology, innovative technology, special teachers, readiness of special teachers.